The Business Digitalization Model to Enhance Family Business Performance - Ricky Adrian Gunawan; Andika Pratama; Arta Moro Sundjaja (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Digital transformation is changing how an organization uses technology, enterprise, processes, and people to improve performance and adopt a new business model. Digital transformation drives value through shared industry information and insights. However, several limitations, such as differences in culture and perspective between owners and management, impede the implementation of this digitalization. Harmonization is needed to keep the changes from getting out of hand because the digitization process is affected not only by sales, marketing, and finance processes but also by the culture of digitization. This study investigates the impact of digital organizational culture, digital capabilities, digital technology, and digital transformation strategy on the performance of family businesses. The research design is a quantitative study with structural equation modeling. The population in this study cannot be determined due to limited access to the association. The sample size was calculated using the G-Power calculator with an effect size of 0.15, an alpha level of 0.05, and a power of 0.80. According to the calculation, there are 43 respondents in the study. The sampling technique is convenient sampling. The survey was distributed online using questionnaires sent via email. The data analysis software is Smart PLS 4.0.8.5. The result shows that the organization's culture plays a big part in improving performance. The organization's culture strongly affects business digitization and technology value development. The value of developed technology affects business performance. Therefore, the top management needs to prioritize the IT development that transforms their business and improves business performance